Systematic review of the factors and the key indicators that identify doctors at risk of complaints, malpractice claims or impaired performance - Frances Rapport; Jeffrey Braithwaite; Peter D Hibbert; Yvonne Tran; Robyn Clay-Williams; Janet C Long; Gaston Arnolda; Louise K Wiles; Reidar P Lystad; Elizabeth E Austin; Vu Do; Ruqaiya Nullwala; et al. (BMJ Open)
Objective To identify the risk factors associated with complaints, malpractice claims and impaired performance in medical practitioners.Design Systematic review.Data sources Ovid-Medline, Ovid Embase, Scopus and Cochrane Central Register of Controlled Trials were searched from 2011 until March 2020. Reference lists and Google were also handsearched.Results Sixty-seven peer-reviewed papers and three grey literature publications from 2011 to March 2020 were reviewed by pairs of independent reviewers. Twenty-three key factors identified, which were categorised as demographic or workplace related. Gender, age, years spent in practice and greater number of patient lists were associated with higher risk of malpractice claim or complaint. Risk factors associated with physician impaired performance included substance abuse and burn-out.Conclusions It is likely that risk factors are interdependent with no single factor as a strong predictor of a doctor’s risk to the public. Risk factors for malpractice claim or complaint are likely to be country specific due to differences in governance structures, processes and funding. Risk factors for impaired performance are likely to be specialty specific due to differences in work culture and access to substances. New ways of supporting doctors might be developed, using risk factor data to reduce adverse events and patient harm.PROSPERO registration number PROSPERO registration number: CRD42020182045.